Development of an indirect ELISA assay to evaluation of the adaptive immune response of pacu (Piaractus mesopotamicus) - Farias, Thais H.v.; Silva, Ketherson R.; Mariguela, Viviane C.; Montassier, HÉlio J.; Pilarski, Fabiana (Academia Brasileira de Ciências, 2018)
ABSTRACT The pacu is one of the most important species for Brazilian fish farming and is considered emerging in the global aquaculture. Despite its importance, no effective tool for evaluation of the adaptive immune response of this species has been developed. Therefore, this study aimed the development and standardization of indirect ELISA for the measurement of pacu antigen-specific antibodies using polyclonal rabbit anti-pacu IgM used as detector antibody. For this purpose was isolated and purificated of pacu IgM using mannose-binding protein affinity chromatography and produced specific polyclonal antibodies against heavy and light chains pacu IgM, that showed a molecular weight of 72 kDa and 26 kDa, respectively. Polyclonal antibodies obtained demonstrated specificity with heavy and light Ig chains of pacu serum in western blotting. These polyclonal antibodies allowed the development of an indirect ELISA assay of high sensitivity and specificity for the detection and quantification of pacu IgM antibodies immunized with bovine IgG. In conclusion, this approach has great potential to improve the monitoring of vaccine-induced immune responses and help develop immunodiagnostic and epidemiological studies of infectious diseases in pacu systems.
Keywords: ELISA; Immunoglobulin; Pacu`s immune system; Polyclonal antisera